2014
DOI: 10.1158/1535-7163.mct-14-0475
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Penetration and Activity of Camptothecins in Solid Tumor Xenografts

Abstract: The ability of a panel of camptothecin derivatives to access the tumor compartment was evaluated to determine the mechanisms by which the architecture of solid tumors may act to limit their activity. Microregional localization and activity of members of the camptothecin class of topoisomerase I targeting agents, including topotecan, irinotecan, and irinophore C, a lipid-based nanoparticulate formulation of irinotecan, were evaluated over time in HCT116 and HT29 colorectal tumor xenografts. Using native drug fl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 31 publications
2
10
0
Order By: Relevance
“…The level of caspase-3 activity was comparable to the level observed from cells treated with camptothecin, a pro-apoptotic drug commonly used as a positive control in caspase assays. 59 In contrast, free anti-miR-21 LNA and CGKRK−pSiNPs loaded with a scrambled LNA did not result in any significant increase in caspase-3 activity relative to untreated cells ( Figure 2C). Treatment of OAW42 cells with anti-miR-21 CGKRK−pSiNPs led to a significant decrease in cell viability (∼50%), which demonstrated the potential efficacy of the anti-miR strategy in generating a therapeutic effect ( Figure 2D).…”
Section: Research Articlementioning
confidence: 88%
“…The level of caspase-3 activity was comparable to the level observed from cells treated with camptothecin, a pro-apoptotic drug commonly used as a positive control in caspase assays. 59 In contrast, free anti-miR-21 LNA and CGKRK−pSiNPs loaded with a scrambled LNA did not result in any significant increase in caspase-3 activity relative to untreated cells ( Figure 2C). Treatment of OAW42 cells with anti-miR-21 CGKRK−pSiNPs led to a significant decrease in cell viability (∼50%), which demonstrated the potential efficacy of the anti-miR strategy in generating a therapeutic effect ( Figure 2D).…”
Section: Research Articlementioning
confidence: 88%
“…Importantly, to simulate the clinical situation, where most tumor cells only receive only sub-toxic chemotherapy drug concentrations, [11][12][13] we used, in our subsequent in vitro studies, cisplatin concentrations that would not trigger killing of ovarian cancer cells in vitro and in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…10 A series of studies demonstrated that intravenously injected chemotherapy drugs penetrate only a few cell layers from the blood vessel into the tumor. [11][12][13] This implies that more distant tumor cells are exposed to lower drug concentrations that are non-cytotoxic. It is thought that this triggers the formation of CSC that later drive cancer recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…However the 5-year survival rate only reaches 18% [3]. The poor efficacy of the treatments results from the late diagnosis and from the limited and nonspecific access of chemotherapeutics to lung tumors after intravenous administration [4,5]. Pulmonary delivery is considered an attractive route of administration for chemotherapeutic agents, with the advantages of direct drug deposition at the diseased site and low systemic side effects.…”
Section: Introductionmentioning
confidence: 99%